Effects of municipal solid waste incineration fly ash on solidification/stabilization of Cd and Pb by magnesium potassium phosphate cement. Issue 1 (March 2016) - Su, Ying; Yang, Jianming; Liu, Debin; Zhen, Shucong; Lin, Naixi; Zhou, Yongxin
Highlights: Cd leaching concentration increased when added MSWI FA. Pb leaching concentration decreased first and then increased when added MSWI FA. Leaching concentration met the standard below 40% addition of MSWI FA. All MKPC pastes exhibited high compressive strength. MSWI FA exhibited synergistic and lesser effect on S/S of Pb and Cd, respectively. Abstract: Magnesium potassium phosphate cement (MKPC) is a novel agent for solidification/stabilization (S/S) of heavy metals. In this study, different ratios of municipal solid waste incineration fly ash (MSWI FA) were added to MKPC as an admixture to solidify/stabilize heavy metal in an attempt to reduce S/S cost while also disposing and reusing the MSWI FA. The effects of MSWI FA on different heavy metals, including Cd, Pb and a Cd–Pb mixture, were also investigated. The results showed that Cd leaching concentration increased gradually with increasing MSWI FA upon S/S of Cd or Cd–Pb mixtures, while Pb leaching concentration decreased, then increased for Pb and Cd–Pb mixtures. After curing for 90 d, the compressive strength of all MKPC pastes decreased gradually with increasing MSWI FA. Generally, a percentage of MSWI FA below 40% is suitable for being used as an admixture of MKPC to S/S heavy metals, and less than 20% is suggested for being used as a component of construction material. As an admixture of MKPC, MSWI FA exhibited an obviously synergistic effect on S/S of Pb, while it had a lesser effect on S/S of Cd, primarily because of its great adsorption characteristics and chemical fixation of Pb.